(untitled) (Journal of the College of Basic Education, 2023)
Sabeans: the name of a very old religious sect whose followers still adhere to special religious beliefs and rituals.It has sacred books, and it is a multi-sect, the most famous of which is Mandaean, which believes in God and the Last Day.It believes in rewards and punishments in Heaven and Hell. However, this belief (in their view) was not acquired throughThe tongue of a prophet but towards the divine outpouring (knowledge).Mandaeans believe that spiritual (angels) influence the fate of the living.Some of them work as assistants to the Divine Self in the process of creation and management of the affairs of the universe.Planets and stars are their headquarters, hence the Sabeans’ veneration of planets and stars.Not because of the stars, but because of their spirituality, and for that reason the ancient researchers called them((People of Spirituality))And the spiritual ones are the subject of our research, while standing on the meaning of the Sabians in the languageAnd the definition of their upbringing and the statement of the opinions of their other teams and their books and a statement mentioned in the Holy Quran.After this reading of the Sabian beliefs, I devoted my effort to researching it, and I have a nucleus for a projectMore comprehensive research on this group.If I am right, then that is the success of God Almighty, even if it is the second, only the effort that I made and the safety of me.My intention and praise be to God, Lord of the worlds